VD_FINDINFO HC / 2016 / 425 vom 28. Juni 2016 - VD Tribunal cantonal (2016)
HARCÈLEMENT PSYCHOLOGIQUE, DROIT DE LA FONCTION PUBLIQUE, PREUVE FACILITÉE, ENQUÊTE ADMINISTRATIVE | 328 CO, 5 al. 3 LPers-VD, 57 al. 1 LPers-VD, 61 LPers-VD, 142 al. 1 RLPers-VD, 142 al. 2 RLPers-VD, 3 RCTH